Characterizing the diversity of aromatics in a coflow diffusion Jet A-1 surrogate flame. (15th May 2020) - Saldinger, Jacob C.; Wang, Qi; Elvati, Paolo; Violi, Angela
Abstract: Understanding the formation of soot precursors requires properly taking into account their diverse structure and chemistry. To study the extent of this variety in a realistic combustion system, we simulated the growth of polycyclic aromatic compounds (PACs) in a diffusion coflow flame using a three-component Jet A-1 surrogate ( n -decane/ propylbenzene/ propylcyclohexane) as fuel. A kinetic Monte Carlo software, which generates samples of the atomistic evolution of gas-phase molecules' growth, was used to characterize the PACs' growth in this flame. We leveraged our simulations to identify a number of aromatic structures. In addition to aromatic hydrocarbons, we were able to reproduce the diverse array of oxygenated PACs observed experimentally between 150u and 450u, specifically a number of PACs with five-membered carbon rings and furan, hydroxl, and ketone groups. The amount of PACs with masses between 450u and 600u was slightly over-predicted, indicating that in this mass range there are possibly other mechanisms ( e.g., radical-radical interactions) that reduce the concentration of these PACs. As our growth mechanism is focused mostly on aromatic growth, we did not observe the more aliphatic molecules seen in experiment. Overall, our results suggest that there is a wide range of structures with different degrees of oxygenation and aromaticity that must be accounted for when modeling PACs' growth in combustion environments.